Hemodynamic Consequence of Hand Ventilation Versus Machine Ventilation During Transport After Cardiac Surgery. Issue 5 (October 2017) - O'Brien, E. O.; Newhouse, B. J.; Cronin, B.; Robbins, K.; Nguyen, A. P.; Khoche, S.; Schmidt, U.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 31(4):1246–1249, 2017) Manual hand ventilation and portable machine ventilation are both widely used during in-hospital transport of intubated patients following surgery, but the comparative safety and reliability of each mode of ventilation are still unclear. This prospective randomized study aimed at examining the hemodynamic consequences of manual and portable ventilation during transport from the operating room (OR) to the intensive care unit (ICU) in intubated patients following cardiac surgery.